Eksperimentasi Pendekatan RME terhadap Prestasi Belajar Matematika Ditinjau dari Motivasi Belajar Siswa - Rofiq Suprayogo; Sutrisno Sutrisno; Supandi Supandi (Universitas PGRI Semarang, 2019)
The purpose of this research is to determine the effect of Realistic Mathematic Education on mathematics learning achivement in terms of student motivation. The research design used in this research is Quasi Experimental Design with factorial 2 × 3. Sampling by Cluster Random Sampling technique. The population in this study is all students of class IX in MTS Futuhiyyah 1 Mranggen. The data in this study is obtained from the posttest result of mathematics learing achivement and questionnaire of student motivation. Data processing is done by using anova calculation of two different cell paths followed by scheffe test '. The conclusions of the results of data processing are (1) Student achievement in kesjangunanan material and kekongruenan using learning approach Realistic Mathematic Education provides better learning achievement compared with conventional approach, (2) highly motivated students have better learning achievement than low motivated students, and students with moderate motivation have better learning outcomes than students with low motivation, and (3) there is no interaction between learning models with student motivation on student achievement.